Review of the genus Eurypteryx C. Felder & R. Felder, 1874 from China, with a first description of the male E. dianae (Lepidoptera: Sphingidae) - Jiang, Zhuo-Heng; Wang, Cheng-Bin (Zootaxa, 2020)
The two species of the genus Eurypteryx C. Felder & R. Felder, 1874 known from China, E. bhaga and E. dianae (Lepidoptera, Sphingidae, Macroglossinae, Macroglossini) were examined and compared with E. geoffreyi from Thailand. The male E. dianae is described for the first time based on a single specimen from an evergreen broad-leaf forest in Maolan Nature Reserve, Libo, Guizhou, China. The diagnostic features and a distribution map of the species of Eurypteryx in China are provided. A list of all Eurypteryx species presently known worldwide is also given.